PP.20.35: CARDIO-ANKLE VASCULAR INDEX (CAVI) AND QUALITY OF LIFE EVALUATED USING THE SF-12 QUESTIONNAIRE. MARK STUDY. (June 2015) - Garcia-Ortiz, L.; Ramos-Blanes, R.; Ramos-Delgado, E.; Recio-Rodriguez, J.I.; Gil-Gregorio, A.; Santos-Polo, S.; Hernandez-Juanes, F.J.; Alba-Perez, I.; Martinez-Martinez, L.M.; Moreno-Gonzalez, M.P.; Rodriguez-Martín, C.; Castaño-Sanchez, C.; et al.
Abstract : Objective: To analyse the relationships between Cardio-Ankle Vascular Index and quality of life in patients with intermediate cardiovascular risk. Design and method: We performed a cross sectional study including 500 subject, aged 30 to 75 years (mean: 60.31 ± 8.44), 54.4% men, without cardiovascular diseases from the MARK study, selected by consecutive sampling from a Spanish health centre. Measurement: Cardio-AnkleVascular Index (CAVI) by VaSera device (Fukuda Denshi). Quality of life evaluated using the SF-12 questionnaire. Results: The CAVI mean was 8.59 ± 1.03, in men 8.62 ± 1.16 and in women 8.55 ± 1.03 (p > 0.05). The 29.3% were less than 8 (normal), the 36.6% were between 8 y 9 (border line) and the 34.1% were equal or higher than 9 (Atherosclerosis probably). The SF12 results were: Physical function 50.7 ± 9.0; Role physical 50.9 ± 9.2 Bodily pain 49.8 ± 1.7; General health 39.9 ± 8.9; Vitality 51.1 ± 1.1; Social functioning 49.9 ± 9.8; Role emotional 48.9 ± 9.7; Mental health 49.7 ± 10.5; Standardized Physical component 48.4 ± 9.3; Standardized Mental component 49.5 ± 10.5. Standardized Physical component in subject with CAVI < 8 was 46.53 ± 11.02; 8–9: 48.44 ± 9.39 and > 9: 50.08 ± 7.09; p = 0.023. Standardized Mental component in subject with CAVI < 8 was 49.39 ± 10.88; 8–9: 51.67 ± 8.91 and > 9: 51.67 ± 8.91; p < 0.011. CAVI was positively correlated with Physical function (r = 0.168, p = 0.003), Role physical (r = 0.180, p = 0.001), Bodily pain (r = 0.192, p = 0.001), General health (r = 0.118, p = 0.037), Social functioning (r = 0.119, p = 0.037), Mental health (r = 0.157, p = 0.006) and Standardized Physical component (r = 0.178, p = 0.002), but not with Standardized Mental component (r = 0.082, p = 0.149). In multiple lineal regression analysis(GLM), considering CAVI as independent variable and adjusted by age, sex, statin and antihypertensive drugs, remained statistical signification Physical function (Beta 1.872, p = 0.001), Role physical (Beta 1.275 p = 0.024), and Standardized Physical component (Beta 1.667, p = 0.004). Conclusions: The Cardio-Ankle Vascular Index is directly associated with Physical function, Role physical and Standardized Physical component but not with Mental components of quality of life questionnaire. Future studies are needed to clarify this unexpected finding.